2016
DOI: 10.1016/j.jlumin.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The role of cerium variable charge state in the luminescence and scintillation mechanism in complex oxide scintillators: The effect of air annealing

Abstract: a b s t r a c tThe influence of annealing in air at elevated temperatures on the absorption, luminescence and scintillation characteristics was studied for a set of Ce-doped aluminum garnet and perovskite single crystals. Positive effects consisting mainly in increase of light yield and decrease of afterglow were found to varying extent in all the materials. It is explained by the positive role of created stable Ce 4 þ center in scintillation mechanism and by decrease of deep trap concentration based on oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…[ 125,126 ] However, the onset of thermal quenching is considerably lowered, which limits their usage to room temperature applications. [ 135 ] The positive role of Ce 4+ in the scintillation mechanism in orthosilicates has recently been reported in the literature (see Section 3.3 below) and the same mechanism apparently also functions in garnets. [127][128][129][130] Interestingly, another strategy preserving the high-temperature stability of cerium emission centers has recently been formulated to approach the problem of electron trapping in the transfer stage of the scintillation mechanism in garnet scintillators.…”
Section: Reviewmentioning
confidence: 65%
See 1 more Smart Citation
“…[ 125,126 ] However, the onset of thermal quenching is considerably lowered, which limits their usage to room temperature applications. [ 135 ] The positive role of Ce 4+ in the scintillation mechanism in orthosilicates has recently been reported in the literature (see Section 3.3 below) and the same mechanism apparently also functions in garnets. [127][128][129][130] Interestingly, another strategy preserving the high-temperature stability of cerium emission centers has recently been formulated to approach the problem of electron trapping in the transfer stage of the scintillation mechanism in garnet scintillators.…”
Section: Reviewmentioning
confidence: 65%
“…[ 148 ] The recent systematic study of light yield and other characteristics in Prdoped (Lu x Y 1-x ) 3 Al 5 O 12 showed an enormous increase of light yield up, to 33 000 photons MeV −1 for a 1 mm-thick sample of (Lu 0.75 Y 0.25 ) 3 Al 5 O 12 :Pr. [ 135,151 ] Despite the fact that this review is devoted to single-crystal materials, the following paragraph is devoted to garnet-based scintillation ceramics, as they have appeared as serious competitors to the single crystals of the garnet scintillators described above. [ 149 ] An additional positive effect that might contribute to the light yield increase would be due to the solid solution host, an effect that has been observed in several material systems.…”
Section: Reviewmentioning
confidence: 99%
“…Since these crystals were grown in different ambient, the defect centers may be considered to play a major role for any change in optical or scintillation properties. The crystals grown in argon are more prone to have defect centers related to the anion sublattices which can be generated either due to oxygen vacancies (F or F + ) or presence of interstitial oxygen (O -) [13,19]. An annealing in air decreases the concentration of these defect centers that consequently increase the light …”
Section: Resultsmentioning
confidence: 99%
“…The light yield of Ce 3þ activated YAG and LuAG has been reported at 25,000 [1] and 20,000 photons/MeV [2], respectively, which are far below the theoretical value of 60,000 photons/MeV calculated by the Bartram-Lempicki equation [3]. Many attempts have been made to find new potential scintillators with high density, high light yield, fast decay time and high stopping power via both experimental and theoretical research.…”
Section: Introductionmentioning
confidence: 96%